1977
DOI: 10.1111/j.1365-3180.1977.tb00454.x
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption and degradation of glyphosate in five Hawaiian sugarcane soils*

Abstract: Summary: The rate of aerobic evolution of 14CO2 from 14C‐glyphosate labelled in the methylphosphonyl carbon, varied 100‐fold within a group of five Hawaiian sugarcane soils. The rate depended inversely on the degree of soil binding, probably associated with the phosphonic acid moiety, and to a less certain extent on soil pH and soil organic matter. After an initial rapid degradation, the rate of 14CO2 evolution in three soils reached a constant at 16–21 days which continued to the 60‐day termination. The other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
1
18

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 5 publications
6
95
1
18
Order By: Relevance
“…McConnell and Hossner (1985) using kaolinite, hematite and goethite and Sheals et al (2002) using goethite also showed that the adsorption of GPS were dependent on the pH GPS/clay system. Nomura and Hilton (1977) and Morillo et al (2000) also showed that adsorption of GPS on soils decreased with an increase in pH. It was due to an increase in negative charge of GPS and mineral surfaces with an increase in pH resulting in a decrease in the adsorption.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…McConnell and Hossner (1985) using kaolinite, hematite and goethite and Sheals et al (2002) using goethite also showed that the adsorption of GPS were dependent on the pH GPS/clay system. Nomura and Hilton (1977) and Morillo et al (2000) also showed that adsorption of GPS on soils decreased with an increase in pH. It was due to an increase in negative charge of GPS and mineral surfaces with an increase in pH resulting in a decrease in the adsorption.…”
Section: Discussionmentioning
confidence: 93%
“…However, there is no agreement about the most important factors that control the adsorption of GPS. Several authors also studied the effect of pH on the adsorption of GPS by soils or clays and they agreed that an increase of pH decreased the adsorption of GPS (Nomura and Hilton, 1977;McConnell and Hossner, 1985;Morillo et al, 2000;Sheals et al, 2002). However, Glass (1987) showed that pH had no effect on the adsorption of GPS by ilite.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of glyphosate-resistant (GR) plants, it has been the most widely used herbicide worldwide [1]. Its half-life under laboratory conditions can range from 30 to 40 days [2][3][4], but in the field can vary from 2 to 197 days [5]. Although it has been found to be quickly degraded by microbial activity [6], its combined ability to adsorb to soil particles and to disperse throughout the soil profile contribute to its accumulation in soils [7].…”
Section: Introductionmentioning
confidence: 99%
“…As recently discussed by Gomes et al (2014a), glyphosate can also indirectly affect other plant physiological processes such as photosynthesis, inducing oxidative stress. In addition to its role in glyphosate uptake, PO 4 3-may play a role in plant response to the herbicide, as it can help them avoid some of the contaminant's deleterious effects. For example, it was observed that by increasing PO 4 3-uptake, plant tolerance to arsenate (which, like glyphosate, is chemically similar to PO 4 -3 ) is increased through activation of antioxidant systems, preventing oxidative burst induced by the trace-element [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were placed on a reciprocal shaker at 20ºC, for four hours, to get the adsorption thermodynamic equilibrium (Sprankle et al, 1975a;Hance, 1976;Nomura & Hilton, 1977;Cheah et al, 1997). Samples were subsequently centrifuged for 20 min at 20,000 rpm at 1ºC (Ultracentrifuge Sorvall OTD-Combi) and the liquid phases were then passed through filter paper (MFS 5c, Whatman 42 equivalent).…”
Section: Methodsmentioning
confidence: 99%